The consuming temple : Jews, department stores, and the consumer revolution in Germany, 1880-1940 - Lerner, Paul Frederick 1966- (Cornell University Press, 2015)
Jerusalem's terrain: the department store and its discontents in imperial Germany -- Dream worlds in motion: circulation, cosmopolitanism, and the Jewish question -- Uncanny encounters: the Thief, the Shop Girl, and the Department Store King -- Beyond the consuming temple: Jewish dissimilation and consumer modernity in provincial Germany -- The consuming fire: fantasies of destruction in German politics and culture